ANALISIS PERBAIKAN DESAIN MESIN PERAJANG EMPONEMPON DENGAN DOUBLE CHOPPER MENGGUNAKAN PENDEKATAN DFMA DAN ANALISIS STRUKTUR - Muhammad Abdul Nashr; Tri Andi Setiawan; Thina Ardliana (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Spices chopping machine with double chopper is a machine that functions to chopper or thinly slice empon-empon using a double chopper. This machine is a development product of the spices chopping machine with one chopper and manual chopper so as to produce high spices chopping production compared to one chopper machine and manually. However, the results of the development of the chopping machine are still quite expensive for the home-scale herbal medicine industry. The application of reducing expenses needs to be applied with consideration to the design of a spices chopping machine with double chopper that is more efficient by taking into account the ease of manufacturing and assembly in accordance with the DFMA technique and analyzing the structure of the lifetime of certain components to keep the machine working optimally. The initial product that has been redesigned creates 2 new designs. From the simulation results of the three spices chopping machine with double chopper design concepts that have been described, it can be concluded that the new design concept 1 meets the three criteria indicated by a safety factor value of 13.08, labor cost 613.50 s, manufacturing cost the lowest is $279.66 and bearing component lifetime is 698.3 months and the lifetime of v-belt components is 1564,045 hours of work, then the design concept that has the best simulation results is the redesign of 1 spices chopping machine with double chopperris.